EFEK INTERAKSI NEGARA PRODUSEN DAN KESADARAN MEREK UNTUK NIAT PEMBELIAN KAUM MUDA PADA PRODUK DENGAN KETERLIBATAN RENDAH - Wahyu Eko Prasetyanto (Exchall: Economic Challenge, 2022)
This study aims to examine the effect of producer country interaction and brand awareness, packaging and price impact on toothpaste purchase intention among young people. As previous studies have shown, country of origin should not be considered a single clue, as this overestimates the country of origin effect. This study evaluates the effect of country of origin (product) on goods with low involvement (in this case toothpaste). The Cue Utilization Theory is used to explain how consumers use product cues to assess a product before making a purchase decision. Research data were analyzed using SmartPLS. The results of this study indicate that all variables affect the consumer's purchase intention of toothpaste. IPMA (Importance and Performance Matrix) analysis shows that the interaction effect of producer countries and brand awareness is an important factor